Fraxetin inhibits interleukin-1β-induced apoptosis, inflammation, and matrix degradation in chondrocytes and protects rat cartilage in vivo - Qing Wang; Di Zhuang; Wenchang Feng; Bitao Ma; Liping Qin; Lilun Jin (Elsevier, 2020)
Osteoarthritis (OA) is a disease characterized by degeneration of the joint complex due to cartilage destruction. Fraxetin, a widely used and studied coumarin compound extracted from a traditional Chinese herb (Qin Pi), has shown anti-inflammatory and antioxidant properties, but its effects on OA have not been studied. In the present study, western blotting, immunofluorescence, and terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) were used to evaluate the effects of fraxetin on IL-1β-induced apoptotic activity, inflammatory responses, and catabolism in rat chondrocytes. The results showed that fraxetin prevented IL-1β-induced apoptosis of chondrocytes and inhibited inflammatory mediator release by regulating the Toll-like receptor 4 (TLR4)/myeloid differentiation primary response 88 (MyD88)/nuclear factor (NF)-κB pathway in chondrocytes. Additionally, fraxetin suppressed the upregulation of matrix metalloproteinase 13 (MMP13) and degradation of collagen II in the extracellular matrix (ECM). Moreover, the effects of fraxetin in vivo were assessed in a monosodium iodoacetate (MIA)-induced rat model of OA using hematoxylin and eosin (H&E) and Safranin O-fast green staining and magnetic resonance imaging (MRI). The results showed that fraxetin protected the cartilage against destruction. In conclusion, fraxetin could be a potential therapeutic for OA.